Intradiverticular Sarcomatoid Carcinoma of The Bladder: An Overview Starting From A Peculiar Case. - Lembo, Francesco; Subba, Enrica; Laganà, Antonio Simone; Vitale, Salvatore Giovanni; Valenti, Gaetano; Magno, Carlo (Urology Journal, 2016)